Real‐world experience with decitabine as a first‐line treatment in 306 elderly acute myeloid leukaemia patients unfit for intensive chemotherapy. Issue 4 (20th August 2019) - Bocchia, Monica; Candoni, Anna; Borlenghi, Erika; Defina, Marzia; Filì, Carla; Cattaneo, Chiara; Sammartano, Vincenzo; Fanin, Renato; Sciumè, Margherita; Sicuranza, Anna; Imbergamo, Silvia; Riva, Marta; et al.
Abstract: Despite widespread use of decitabine to treat acute myeloid leukaemia (AML), data on its effectiveness and safety in the real‐world setting are scanty. Thus, to analyze the performance of decitabine in clinical practice, we pooled together patient‐level data of three multicentric observational studies conducted since 2013 throughout Italy, including 306 elderly AML patients (median age 75 years), unfit for intensive chemotherapy, treated with first‐line decitabine therapy at the registered schedule of 20 mg/m 2 /iv daily for 5 days every 4 weeks. Overall response rate (ORR), overall survival (OS) curves, and multivariate hazard ratios (HRs) of all‐cause mortality were computed. Overall, 1940 cycles of therapy were administered (median, 5 cycles/patient). A total of 148 subjects were responders and, therefore, ORR was 48.4%. Seventy‐one patients (23.2%) had complete remission, 32 (10.5%) had partial remission, and 45 (14.7%) had haematologic improvement. Median OS was 11.6 months for patients with favourable‐intermediate cytogenetic risk and 7.9 months for those with adverse cytogenetic risk. Median relapse‐free survival after CR was 10.9 months (95% confidence interval [CI]: 8.7‐16.0). In multivariate analysis, mortality was higher in patients with adverse cytogenetic risk (HR=1.58; 95% CI: 1.13‐2.21) and increased continuously with white blood cell (WBC) count (HR=1.12; 95% CI: 1.06‐1.18). A total of 183 infectious adverse events occurred in 136 patients mainly (>90%) within the first five cycles of therapy. This pooled analysis of clinical care studies confirmed, outside of clinical trials, the effectiveness of decitabine as first‐line therapy for AML in elderly patients unfit for intensive chemotherapy. An adverse cytogenetic profile and a higher WBC count at diagnosis were, in this real life setting, unfavourable predictors of survival.